2021
DOI: 10.4194/1303-2712-v21_12_01
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Length-Weight Relations, and Condition Factor of Sea Cucumbers in Three Coastal Areas Along the Southern Coast of Sri Lanka: A Case Study

Abstract: Economically and ecologically important ecosystems that consist of diverse finfish and shellfish resources are found along the southern coast of Sri Lanka. Thus, the current study intends in assessing the species diversity, length-weight (L-W) relationships, and condition factor of sea cucumber stocks in selected coastal sites of southern Sri Lanka. The diversity of sea cucumber species was surveyed using the systematic sampling technique in three selected sites (Bandaramulla, Mirissa, and Weligama) during Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Negative allometric growth of the H. atra was also found in the waters of Karimunjawa (Panuluh et al, 2019), in the waters of Panjang Island (Jepara) (Permata et al, 2021), in the waters of Ambon, Saparua, Osi and Marsegu Islands, Maluku Province as well (Luhulima et al, 2020). On other regions such as Morela waters in Maluku Province (Ongkers et al, 2018) and in Sri Lanka respectively found the similar results (Gamage et al, 2021;Veronika et al, 2018). The negative allometric growth of B. marmorata is in accordance with that of found by Luhulima et al, (2020) Negative allometric growth patterns are often found in other sea cucumber species from the genus Holothuria (Ahmed et al, 2018;Veronika et al, 2018;Aydin, 2020), Sticophus cf.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Negative allometric growth of the H. atra was also found in the waters of Karimunjawa (Panuluh et al, 2019), in the waters of Panjang Island (Jepara) (Permata et al, 2021), in the waters of Ambon, Saparua, Osi and Marsegu Islands, Maluku Province as well (Luhulima et al, 2020). On other regions such as Morela waters in Maluku Province (Ongkers et al, 2018) and in Sri Lanka respectively found the similar results (Gamage et al, 2021;Veronika et al, 2018). The negative allometric growth of B. marmorata is in accordance with that of found by Luhulima et al, (2020) Negative allometric growth patterns are often found in other sea cucumber species from the genus Holothuria (Ahmed et al, 2018;Veronika et al, 2018;Aydin, 2020), Sticophus cf.…”
Section: Resultsmentioning
confidence: 56%
“…The condition factor values obtained by H. atra on Moti Island was higher than the other two types of sea cucumbers. According to Gamage et al, (2021), the highest condition factor value for sea cucumbers recorded at a location indicates that the local environmental conditions are favourable and support the physical health of the individual organism. In addition, sea cucumbers with a higher condition factor values are expected to have higher fecundity than sea cucumbers with a low condition factor, because this is a form of adaptation to maintain their sustainability in nature.…”
Section: Resultsmentioning
confidence: 99%
“…Sea cucumbers are marine invertebrates of the family Holothuroidea, that possess unique morphological characteristics such as leathery skins, feeding tentacles and elongated bodies, which aid in their survival as bottom detritus feeders (Idreesbabu & Sureshkumar 2017;Mohammednowshad et al 2021). These animals play an important role as a biotic component in the benthic zone of coastal marine ecosystems (Gamage et al 2021) by regulating micro-algae growth, nutrient recycling and mixing the upper sediment layers through bioturbation (Costa et al 2014;Arnull et al 2021). These ecological interactions also allow the sea cucumbers to inhabit soft bottom coral reef areas and intertidal seagrass ecosystems (Navarro et al 2014;Floren et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This positive association between declining sea cucumber populations of India and intertidal seagrass species also emphasizes the need for continuous monitoring of seagrass ecosystems of ANI and India, and maintain the health of these seagrass ecosystems, which are under decline in Neil and Havelock islands of ANI (Mishra & Apte 2020;Mishra et al 2021). The decline of intertidal keystone systems and their J TT negative effects on sea cucumber population of India have been documented from the islands of Lakshadweep (Idreesbabu & Sureshkumar 2017;Mohammednowshad et al 2021) and Gulf of Mannar region of Sri Lanka (Gamage et al 2021) showcasing the ecosystem services of these systems to India's declining sea cucumber populations. Similarly, migration of endangered H. scabra from South Andaman to Ritche's Archipelago also calls for monitoring and of other island systems of ANI to assess the presence of this species and create subsequent protection and management action plans.…”
mentioning
confidence: 99%